2022
DOI: 10.3389/fpsyg.2022.992497
|View full text |Cite
|
Sign up to set email alerts
|

How teacher and classmate support relate to students’ stress and academic achievement

Abstract: According to the conservation of resources theory, social support provides resources to help overcome challenges. Although some empirical findings have emphasized the pivotal role of teacher support and/or peer support for students’ stress and academic achievement, multilevel analyses that consider contextual class and individual student effects are scarce. The current study addresses this gap and further includes gender, socio-economic status, and neuroticism as covariates. Multilevel analyses in Mplus were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 77 publications
1
9
0
Order By: Relevance
“…Teacher autonomy support also positively influenced nursing students' intrinsic motivation, study effort, and perceived learning outcomes, which align with the findings of Torbergsen et al (2023), who suggested that faculty members must promote active and student‐centered learning to further promote their autonomy. Moreover, students who perceived their teacher as autonomously supportive had higher academic performance, consistent with the results of Hoferichter et al (2022) who found that teacher support might affect students' academic performance. Similar findings were also reported by Tennant et al (2015), who discovered that teacher support was positively related to students' GPA.…”
Section: Discussionsupporting
confidence: 89%
“…Teacher autonomy support also positively influenced nursing students' intrinsic motivation, study effort, and perceived learning outcomes, which align with the findings of Torbergsen et al (2023), who suggested that faculty members must promote active and student‐centered learning to further promote their autonomy. Moreover, students who perceived their teacher as autonomously supportive had higher academic performance, consistent with the results of Hoferichter et al (2022) who found that teacher support might affect students' academic performance. Similar findings were also reported by Tennant et al (2015), who discovered that teacher support was positively related to students' GPA.…”
Section: Discussionsupporting
confidence: 89%
“…Considering anxiety, the few studies covering anxiety and social support did not detect differences [58,59]. Hoferichter and Raufelder [60] found in their longitudinal study that specific forms of teacher support, such as social-emotional support, academic-learning support, rewards, and recognition, are associated with lower anxiety and lower levels of burnout for students. There is a need for further research to look at anxiety and its association with teacher support.…”
Section: Social Support As Key Factor For Mental Healthmentioning
confidence: 95%
“…School belonging may also positively impact self‐esteem (Ibrahim & El Zaatari, 2020), as students who feel valued and accepted are more likely to develop a positive self‐image; this in turn may protect them from a host of mental health difficulties. A supportive school environment can also help reduce stress levels (Hoferichter et al., 2022) which in turn positively affects physical health. Students with a strong sense of school belonging may be less likely to engage in risky behaviours such as substance abuse (Ahmadi et al., 2020) and may also be more likely to engage in health‐promoting behaviours, such as regular exercise and a balanced diet.…”
Section: Discussionmentioning
confidence: 99%